2015
DOI: 10.1021/acs.langmuir.5b00101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NOM on Oxidative Reactivity of Manganese Dioxide in Binary Oxide Mixtures with Goethite or Hematite

Abstract: MnO2 typically coexists with iron oxides as either discrete particles or coatings in soils and sediments. This work examines the effect of Aldrich humic acid (AHA), alginate, and pyromellitic acid (PA) as representative natural organic matter (NOM) analogues on the oxidative reactivity of MnO2, as quantified by pseudo-first-order rate constants of triclosan oxidation, in mixtures with goethite or hematite. Adsorption studies showed that there was low adsorption of the NOMs by MnO2, but high (AHA and alginate) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 47 publications
(121 reference statements)
6
47
1
Order By: Relevance
“…Similar to our previous work, 23 the reactivity of MnO 2 is slightly higher in the presence of 0.2 mg-C/L of AHA or 0.5 mg-C/L of LHA (Figures 6a,b). This is mostly due to the formation of soluble HA-Mn complexes which inhibits the adsorption of the produced Mn 2+ during MnO 2 reaction.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Similar to our previous work, 23 the reactivity of MnO 2 is slightly higher in the presence of 0.2 mg-C/L of AHA or 0.5 mg-C/L of LHA (Figures 6a,b). This is mostly due to the formation of soluble HA-Mn complexes which inhibits the adsorption of the produced Mn 2+ during MnO 2 reaction.…”
Section: Resultssupporting
confidence: 90%
“…4 Addition of more than 2 mg-C/L of AHA and LHA increasingly inhibited the MnO 2 reactivity, mostly due to more HAs adsorbed by MnO 2 . 23 Some previous studies have made similar observations which have been attributed to the blockage of MnO 2 surface sites. 1 As presented in our previous paper, 23 both alginate and PA did not affect MnO 2 reactivity, likely because of their poor adsorption by MnO 2 under the experimental conditions.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Recent studies have also shown that media temperature can influence zeta potential [15,187]. Zeta potential is commonly determined by measuring electrophoretic mobility, the velocity of a particle in a unit electric field, using instruments such as Malvern Zetasizer Nano [91,146,[188][189][190][191] and Brookhaven Zetaplus [192]. Zeta potential is related to the electrophoretic mobility via the Henry equation:…”
Section: Zeta Potentialmentioning
confidence: 99%